Transformations of leadership - Rooke, David (2005)
Suggests that different leaders exhibit different kinds of action logic i.e. ways in which they interpret their surroundings and react when their power or safety is challenged. Focuses on seven types of action logics. Looks therefore at each leadership style in turn, starting with the least productive.